Design of a charge regulator for application in an isolated micro grid with photovoltaic generation - Gómez Paez, Luís Miguel; Guacaneme Muñoz, Wilmer Eduardo; Rodriguez Benavides, Andrés Felipe; Santamaría Piedrahita, Francisco; Trujillo Rodríguez, Cesar Leonardo (Scientia et Technica, 2018)
This paper presents the design of a charge regulator operating in an isolated micro grid with photovoltaic generation. The converter selected for this application is a SEPIC with a MPPT algorithm for the cases in which the energy demand is greater than the energy available. The algorithm is able to modify its point of maximum power, in order to perform the recharging and supply of power to the battery bank of the system (isolated microgrid) and a group of charges set at a level of determined of voltage. Finally, the results of the tests carried out are presented and the conclusions are given.